Gauge mechanical model in N dimensions - Bouzas Arteche, Antonio Osvaldo (1992)
The Christ-Lee mechanical model is generalized to N spatial dimensions. Its quantization as a gauge system is carried out, emphasizing the relationship between gauge-fixing and curvilinear coordinates in configuration space.